KETERAMPILAN KOMUNIKASI EFEKTIF DALAM MEMPERSIAPKAN GENERASI EMAS 2045 DI SMP KRISTEN 1 SALATIGA - Wardaningsih, Agustin Diana; Senjaya, Jessica Ariella; Patriotika, Reffeltha Achristy; Esra, Greascia Agustina (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Communication skills for the young generation are one of the efforts to prepare capabilities for Indonesia's Golden Generation 2045. One way is through public speaking skills, so that the younger generation is capable and self-confident, especially in the world of work, enabling them to contribute to economic strengthening. The Community Service (PkM) Team from the Communication Science Study Program, FISIP, conducted a Public Speaking Training activity to help boost the self-confidence of junior high school teenagers in Bendosari Hamlet, Salatiga. The purpose of this activity was to develop and hone the students' communication skills so that they have the ability and confidence to express opinions, interact in the classroom, and even utilize the digital world related to social media positively. The implementation method included three stages: (1) needs assessment through observation and interviews; (2) execution of public speaking training covering message delivery techniques, audience mastery, and structuring effective communication content; and (3) evaluation through presentation simulations and participant feedback. The results of the activity showed a significant increase in the participants' self-confidence and ability to convey ideas. This training not only equipped students with practical communication skills but also instilled an awareness of the role of the younger generation in driving sustainable development towards Indonesia's Golden Generation 2045.